Biodegradation of pyrene by pseudomonas sp. JPN2 and its initial degrading mechanism study by combining the catabolic nahAc gene and structure-based analyses. (December 2016) - Jin, Jingnan; Yao, Jun; Zhang, Qingye; Liu, Jianli
Abstract: In this study, a pyrene-degrading bacterial strain Pseudomonas sp. JPN2 was isolated from crude oil in Dagang Oilfield, China. The degrading percent of the strain JPN2 to pyrene was increased with the extension of culture time and achieved a maximum of 82.88% after 25 d culture. Meanwhile, four metabolites 4, 5-dihydroxy-4, 5-dihydropyrene, 4-phenanthrol, 1-hydroxy-2-naphthoic acid and phthalate were detected in the culture solution by GC-MS analysis. In addition, DNA fragments of nahAc gene, encoding α subunit of naphthalene dioxygenase, were amplified by PCR program and sequenced. As a result, it was presumed that the initial cleavage of the aromatic rings on pyrene was occurred at C4 and C5 positions and formed the intermediate 4, 5-dihydroxy-4, 5-dihydropyrene. This issue had been verified by the interaction analysis between pyrene and the active site of naphthalene dioxygenase in the strain JPN2 by molecular docking. Meanwhile, the differences of the amino acid residues in the active sites of template and target enzymes may be a factor leading to the different biological activity between the strain JPN2 and the other bacteria from the genus Pseudomonas . Additionally, the microcalorimetry analysis displayed that the strain JPN2 had high tolerance for pyrene, and the effect could be negligible under the experimental concentration (100 mg L −1 ). Consequently, the strain JPN2 was considered as an excellent candidate for the further bioremediation study of pyrene and the other aromatic contaminants. Highlights: A strain JPN2 with high degradation ability for pyrene was isolated. A crystal structure of naphthalene dioxygenase was built by homology modeling. Interaction between pyrene and active site was analyzed by molecular docking. A combined research method of biological test and theoretical analysis was used.